Does the Pollen Diet Influence the Production and Expression of Antimicrobial Peptides in Individual Honey Bees? - Danihlík, Jiří; Škrabišová, Mária; Lenobel, René; Šebela, Marek; Omar, Eslam; Petřivalský, Marek; Crailsheim, Karl; Brodschneider, Robert (Insects, 2018)
We investigated the importance of protein nutrition for honey bee immunity. Different protein diets (monofloral pollen of Helianthus spp., Sinapis spp., Asparagus spp., Castanea spp., a mixture of the four different pollen and the pollen substitute FeedbeeTM) were fed to honey bees in cages ad libitum. After 18 days of feeding, apidaecin 1 isoforms concentration in the thorax were measured using nanoflow liquid chromatography coupled with mass spectrometry. Expression levels of genes, coding for apidaecins and abaecin in the abdomen were determined using quantitative PCR. The results indicate that protein-containing nutrition in adult worker honey bees can trigger certain metabolic responses. Bees without dietary protein showed lower apidaecin 1 isoforms concentrations. The significantly lowest concentration of apidaecin 1 isoforms was found in the group that was fed no pollen diet when compared to Asparagus, Castanea, Helianthus, and Sinapis pollen or the pollen supplement FeedBeeTM. Expression levels of the respective genes were also affected by the protein diets and different expression levels of these two antimicrobial peptides were found. Positive correlation between concentration and gene expression of apidaecins was found. The significance of feeding bees with different protein diets, as well as the importance of pollen nutrition for honey bee immunity is demonstrated.
Keywords: dietary proteins; Apis mellifera; abaecin; pollen; gene expression; apidaecin